Transkriptionelle Sepsissignatur in Patienten mit Polytrauma - Felix Johannes Thierer; Justus Liebig University Giessen (My University, 2010)
Trotz bester intensivmedizinischer Versorgung sind die Sepsis und derseptische Schock nach einem Trauma mit einer hohen Mortalitätsrate aufIntensivstationen assoziiert. Ursächlich dafür ist unter anderem das fehlendeWissen über die pathophysiologischen Mechanismen der Polytraumaassoziierten Sepsis. Der Mangel am Verständnis spiegelt sich darüber hinaus ineiner späten Diagnose und Risikostratifikation wieder, was vor allem denBeginn einer adäquaten Therapie verzögert.In dieser prospektiven Studie werden Patienten eingeschlossen, die alle miteinem schweren Polytrauma konfrontiert sind (n=26), von denenTranskriptomdaten 12 Stunden nach dem initialen Trauma (Zp0) gewonnenwerden. Dies entspricht einem Zeitraum von 3 bis 5 Tagen vor der klinischenManifestation einer Sepsis. Diese Transkriptomdaten bieten den Vorteil, zumZeitpunkt eines einheitlichen klinischen Phänotyps bereits differenziellebiologische Regulationen aufzuzeigen.Ziel dieser Studie ist es, eine Qualitätssicherungspipeline für Mikroarraydatenzu etablieren und aus dieser Analyse heraus frühzeitig die biologischenUnterschiede zwischen einem komplikationslosen und einem septischenposttraumatischen Krankheitsverlauf aufzuzeigen.Wir verwenden Vollblut, aus welchem mit dem PaxGene System (PreAnalytiX,Heidelberg, Germany) die mRNA isoliert wird und deren Quantität mit demCodeLink UniSet 10K Bioarray (GE Healthcare, Freiburg, Germany) für ca.10.000 verschiedene Gene erfasst wird.Mithilfe der neu entwickelten Qualitätssicherungspipeline verbessern wir dieQualität der Mikroarraydaten signifikant. Die darauffolgende Analyse derTranskriptomdaten zeigt signifikante Unterschiede zwischen imKrankheitsverlauf septischen (S_Pat) und nicht septischen Patienten (NS_Pat).Diese Unterschiede eignen sich als septische Signatur, welche in derClusteranalyse bereits 12 Stunden nach dem initialen Trauma S_Pat undNS_Pat trennen kann. Darüber hinaus zeigen wir, dass in S_Pat zum Zp0bereits einige biologische Funktionen differenziell reguliert sind. Unter anderemzeigt sich eine Dysbalance in der TH1/TH2 Antwort mit einer dominierendenTH2 Antwort. Der unausgeglichene TH1/TH2 Shift zusammen mit derInaktivierung von T Zellen, Neutrophilen, Monozyten und Makrophagen könntenkritische auslösende Faktoren für eine Sepsis sein. Weiterhin zeigen sich eineAktivierung des Zellzyklus und eine Aktivierung der Komplementkaskade.In dieser Studie präsentieren wir eine Pipeline, welche von den Rohdaten bis zuder differenziellen Regulation in der Zukunft die Möglichkeit bietet, qualitativhochwertige standardisierte Mikroarrayanalysen durchzuführen.Mithilfe dieser Pipeline ist es gelungen, eine transkriptionelle Signatur für dieEntwicklung einer Sepsis bereits 12 Stunden nach einem Polytrauma sichtbarzu machen, obwohl die Sepsis sich erst 3-5 Tage später klinisch manifestiert.Durch diese frühzeitig ausgebildete Signatur illustriert diese Arbeit dieNotwendigkeit einer sehr frühen Intervention in potentiell septischen Patienten.Darüber hinaus kann diese Signatur dazu dienen, den späterenposttraumatischen Verlauf vorherzusagen. Transkriptomdaten bieten dieMöglichkeit einer klinischen Applikation in der Zukunft, für die wir sowohlpotentielle diagnostische als auch therapeutische Ansatzpunkte demonstrieren.

Despite best supportive intensive care the development of severe sepsis andseptic shock after trauma still remains associated with a high mortality rate inintensive care units. Our incomplete knowledge of the pathophysiological andbiochemical mechanisms underlying the onset of sepsis in critical care isreflected in the delay of both diagnosis of the condition as well as in thestratification of patients at risk. Thus the severe course of sepsis iscompounded by the inability to initiate adequate therapy in a timely manner.In this prospective study we included 26 patients, with severe multiple trauma,and performed a genome wide transcriptome analysis of cells derived fromperipheral blood 12 hours after the onset of trauma (Zp0). Statistical analysis oftranscriptome data deriving from these patients allowed us to generate asignature expression profile that is predictive of sepsis outcome and precedesits clinical definition, which is based on clinical definitions and organ scores, byat least 3 to 5 days. Indeed at a posttraumatic time point where no clinicaldifferences are apparent, changes at the transcriptome reveal already the onsetof dysfunction of cellular and biological processes.In this study a robust pipeline for the quality-assurance of data deriving fromwhole genome-based transcriptome studies was first established andsubsequently used to analyse large data sets in order to catalogue and uncoverdysfunctional regulation of the cellular pathways and biological processesunderlying questions as to why patients with multiple trauma can havedramatically different outcomes despite suffering similar traumatic insults.In this analysis mRNA isolated from whole blood from patients using thePaxGene System (PreAnalytiX, Heidelberg, Germany) was labeled andhybridized to pre-spotted glass slides harbouring the Codelink Uniset 10kBioarray (GE Healthcare, Freiburg, Germany) for simultaneous quantification ofapproximately 10.000 different genes.The establishment of a workflow incorporating the quality-assurance-pipelinedeveloped in this study enhanced both the quality and robustness of the dataobtained in this study. Thus analysis revealed significant differences betweenpatients confronted by sepsis (S_Pat) and patients with no complications(NS_PAT) in their posttraumatic course. These differences were used to derivea signature for the onset of sepsis following cluster analysis, and also todiscriminate S_Pat and NS_Pat only 12 hours after the initial trauma. Furtherwe were able to show that in S_Pat, biological functions are regulateddifferentially even at this short time period after trauma. It was evident thatpatients who developed sepsis in the course of the disease (3 to 5 days afteradmission), showed an imbalance in the TH1/TH2 response leading to apronounced TH2 response soon after trauma. The imbalanced TH1/TH2response is accompanied by cellular changes that suggest an inactivation ofT cells, neutrophils, monocytes and macrophages whose biological functionsare critical factors for the initiation of processes leading to sepsis. Furthermore,evidence for an enhanced activation of cell cycle genes as well as genesinvolved in activation of the complement cascade were evident.An important outcome of this study is the use of peripheral blood as a source forwhole-genome transcriptome analysis and its suitability in providing informationon biological processes dysregulated during sepsis, the cell types thatcontribute to these changes as well as to provide diagnostic informationallowing us to predict sepsis outcome, at least 3 to 5 days preceding currentlyused clinical scoring systems. Thus transcriptome analysis provides us with awealth of information to generate diagnostic tests that will allow early clinicalintervention in combination with current treatment protocols to amelioratedisease outcome as well as offering possible targets for therapy.
Keywords: Sepsis; Transkriptom; Mikroarray; Polytrauma; ddc:610